Traktatowe podstawy regulacji dotyczących nowej żywności – wybrane zagadnienia - Sokołowski, Łukasz Mikołaj (Wydawnictwo Naukowe UAM, 2015)
This article focuses on the issues related to ensuring the fundamental freedoms and rights in light of the regulation of novel food. Treaty and constitutional regulations have been analysed in comparison with Regulation No 258/97 and new regulation No 2015/2283. The aim of the considerations was to answer the question whether novel food regulations are legally grounded and whether the regulation as such, while anticipating many essential restrictions regarding the launching of innovations in the EU market, does not contradict the fundamental rights, freedoms and constitutional as well as treaty liberties. It is con-cluded that the implementation of a regulation of novel food belongs to the divided compe-tences of the EU and its Member States grounded in Article 114 of the Treaty on the Func-tioning of the European Union.

L’oggetto dell’articolo è costituito dalle questioni legate a garantire diritti fonda-mentali, libertà ed autonomie alla luce delle normative sui nuovi alimenti. Ad analisi sono state sottoposte regolazioni costituzionali e trattatistiche confrontate con il regola-mento n. 2015/2283. L’obiettivo delle considerazioni è di rispondere alla domanda se le regolazioni sui nuovi alimenti fondamento giuridico che confermi la loro legalità e se queste normative, dato che prevedono tante fondamentali limitazioni in materia di introduzione di innovazioni sul mercato dell’Unione europea, non siano in conflitto con i diritti fonda-mentali, le libertà e le autonomie costituzionali e trattatistiche. Nella parte conclusiva l’autore afferma che l’introduzione di regolazioni sui nuovi alimenti rientra tra le competenze condivise tra l’Ue e gli Stati membri. Il fondamento legale è l’articolo 114 del Trattato sul funzionamento dell’Unione europea.
Treaty based regulations of novel food – selected issues
Le basi trattatistiche delle regolazioni sui nuovi elementi – questioni scelte